Associations of handgrip strength with all-cause and cancer mortality in older adults: a prospective cohort study in 28 countries. (25th May 2022) - López-Bueno, Rubén; Andersen, Lars Louis; Calatayud, Joaquín; Casaña, José; Grabovac, Igor; Oberndorfer, Moritz; del Pozo Cruz, Borja
Abstract: Background: mixed evidence exists on the association between muscle strength and mortality in older adults, in particular for cancer mortality. Aim: to examine the dose–response association of objectively handgrip strength with all-cause and cancer mortality. Study Design and Setting: data from consecutive waves from the Survey of Health, Ageing and Retirement in Europe comprising 27 European countries and Israel were retrieved. Overall, 54, 807 men (45.2%; 128, 753 observations) and 66, 576 women (54.8%; 159, 591 observations) aged 64.0 (SD 9.6) and 63.9 (SD 10.2) years, respectively, were included. Cox regression and Fine-Grey sub-distribution method were conducted. Results: during the follow-up period (896, 836 person-year), the fully adjusted model showed the lowest significant risk estimates for the highest third of handgrip strength when compared with the first third (reference) in men (hazard ratio [HR], 0.41; 95% confidence interval [CI], 0.34–0.50) and women (HR, 0.38; 95% CI, 0.30–0.49) for all-cause mortality. We identified a maximal threshold for reducing the risk of all-cause mortality for men (42 kg) and women (25 kg), as well as a linear dose–response association in participants aged 65 or over. No robust association for cancer mortality was observed. Conclusion: these results indicate an inverse dose–response association between incremental levels of handgrip and all-cause mortality in older adults up to 42 kg for men and 25 kg for women, and a full linear association for participants aged 65 years or over. These findings warrant preventive strategies for older adults with low levels of handgrip strength.